Analysis of Scabies Event Based on Personal Hygiene and Occupancy Density in Pondok Gedongsari Village Tegaron Prambon Nganjuk District - Dwi Widayati; Setyo Budi Susanto; Mika Verrnicia Humairo (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Scabies is an infectious disease caused by the infestation of Sarcoptes scabiei variant hominis on the skin which is characterized by itching and skin eruptions. The initial survey at Pondok Gedongsari there were 824 students consisting of 238 students staying at the cottage and 586 students not staying at the cottage and the number of cases in the initial survey was 28 cases. The purpose of this study was to determine the relationship of personal hygiene and environmental sanitation to the incidence of scabies in the Gedongsari Islamic Boarding School, Tegaron Village, Prambon Nganjuk District. The design of this study used a Cross sectional approach. In determining the sample using a sampling technique. The number of samples taken was 149 respondents who stayed at the Pondok. The variables studied were occupancy density, personal hygiene. Based on the bivariate analysis using the Chi-square test, all boarding school administrators are expected to pay more attention to environmental sanitation conditions. Health workers are expected to provide counseling about good environmental variables related to the incidence of scabies disease at the Gedongsari Islamic Boarding School, Tegaron Village, Prambon Nganjuk District, namely personal hygiene, p value = 0.00 and occupancy density p = 0.00 The conclusion of this study is that personal hygiene is 42.95% well behaved and 57.05% is not well behaved, 0.67% occupancy density description meets the requirements and 99.33% does not meet the requirements and there is a relationship between personal hygiene and occupancy density with the incidence of scabies. Researchers hope that all parties in Islamic boarding schools always maintain personal hygiene and residential density. Health workers are expected to provide counseling about good environmental sanitation for Islamic boarding schools and procedures for doing or maintaining good personal hygiene.